A driverless vehicle demonstration on motorways and in urban environments - Godoy, Jorge; Pérez, Joshué; Onieva, Enrique; Villagrá, Jorge; Milanés, Vicente; Haber, Rodolfo (Transport, 2015)
The constant growth of the number of vehicles in today’s world demands improvements in the safety and efficiency of roads and road use. This can be in part satisfied by the implementation of autonomous driving systems because of their greater precision than human drivers in controlling a vehicle. As result, the capacity of the roads would be increased by reducing the spacing between vehicles. Moreover, greener driving modes could be applied so that the fuel consumption, and therefore carbon emissions, would be reduced. This paper presents the results obtained by the AUTOPIA program during a public demonstration performed in June 2012. This driverless experiment consisted of a 100-kilometre route around Madrid (Spain), including both urban and motorway environments. A first vehicle  – acting as leader and manually driven  – transmitted its relevant information  – i.e., position and speed  – through an 802.11p communication link to a second vehicle, which tracked the leader’s trajectory and speed while maintaining a safe distance. The results were encouraging, and showed the viability of the AUTOPIA approach.First published online: 28 Jan 2015